AKTIVA TAK BERWUJUD - Lisvery, Saoria; Ginting, Irma Yosephine (UI Scholars Hub, 2004)
Today, the world is facing a new era. The changing breeze keeps flowing to apprehend a new scheme of business. The new era of business and industry which now focus on information and technology are much more intangible to be measured. They are as well known as intellectual capitals. In addition, the level of business complexity has increased rapidly with the breaching development of intangible assets. Now, assets are valued based not only on their intrinsic beneficiary but also on the effects on the company. Goodwill has been much more familiar in the last decade than before as the merger & acquisition trends are spreading all over the world. A group of assets of a company has been valued more (or less) than its intrinsic value because of many factors. This residual value is treated and known as goodwill. As brand develops and become much stronger, it has its own value. As previously brand was not defined as tangible assets, we did even not know that it actually was an asset. As one of the components of new intangible assets, brand equity has put itself a mark on the financial statement of corporations. This article is intended to give deeper analysis on the development of intangible assets, especially on those described above. With a combination of theories from textbooks and standards, this article will give the readers a new understanding of what intangible asset are and therefore broaden our horizontal perspective in anticipating the arrival of new intangibles that may come, as the environment is still developing.